Ceramic shell foams produced by direct foaming and gelcasting of proteins: Permeability and microstructural characterization by X-ray microtomography. Issue 12 (September 2020) - Stochero, N.P.; de Moraes, E.G.; Moreira, A.C.; Fernandes, C.P.; Innocentini, M.D.M.; Novaes de Oliveira, A.P.
Abstract: In this work, ceramic shell foams produced by direct foaming and gelcasting of proteins containing 35 vol.% of solids were efficiently tailored through the optimization of suspension parameters, foaming and also according to the gelling temperature. These were key parameters employed for controlling the foamability and foam stability, and hence the foam porosity and pore characteristics after the sintering process. The potential of using microtomography in characterizing the morphometric parameters of foams was explored. Airflow permeability measurements (∼24 °C to 727 °C) were performed in order to investigate the applicability of such materials in the fluid flow field. The samples exhibited a wide range of pore sizes (60 ± 5–1700 ± 90 μm), porosity values higher than 80 %, Darcian (k1 ) and non-Darcian (k2 ) permeability coefficients values in the ranges of 1.32–1.83 x 10 −9 m 2 and 8.34–22.46 x 10 -5 m, respectively.